Consumer behavior and payment choice: A conference summary - Marianne Crowe; Scott Schuh; Joanna Stavins (Federal Reserve Bank of Boston, 2006)
The Emerging Payments Research Group (EPRG) at the Federal Reserve Bank of Boston sponsored a new conference, Consumer Behavior and Payment Choice: How and Why Do Consumers Choose Their Payment Methods? on October 27-28, 2005, at the Boston Fed. The conference brought together a diverse set of participants from the academic, private, and public sectors. This paper provides a summary and overview of the conference. Key conclusions are that the consumer's decision-making process concerning payment choice is quite complex, that standard economic models have difficulty incorporating this complexity, that additional research.especially interdisciplinary research.into consumer choice of payment method is needed, and that this conference was an important step in that direction.
Keywords: D11; D12; 330